Artificial Intelligence: Methodology, Systems, and Applications 14th International Conference, AIMSA 2010, Varna, Bulgaria, September 8-10. 2010. Proceedings - Dicheva, Darina; Dochev, Danail; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 14th International Conference on Artificial Intelligence: Methodology, Systems, and Applications, AIMSA 2010, held in Varna, Bulgaria in September 2010.The 26 revised full papers presented together with the 13 posters were carefully reviewed and selected from 93 submissions. The papers are organized in topical sections on knowledge representation and reasoning; intelligent techniques for adaption, personalization, and recommendation; constraints and search; machine learning, data mining, and information retrieval; AI in education; applications.
Knowledge Representation and Reasoning -- Deduction in Existential Conjunctive First-Order Logic: An Algorithm and Experiments -- Use-Based Discovery of Pervasive Services -- Expressive Approximations in DL-Lite Ontologies -- Reasoning Mechanism for Cardinal Direction Relations -- A Framework for Time-Series Analysis -- Intelligent Techniques for Adaptation, Personalization, and Recommendation -- Cross-Language Personalization through a Semantic Content-Based Recommender System -- Towards Effective Recommendation of Social Data across Social Networking Sites -- Term Ranking and Categorization for Ad-Hoc Navigation -- Time Optimized Algorithm for Web Document Presentation Adaptation -- Constraints and Search -- Discrepancy-Based Sliced Neighborhood Search -- Constraint Models for Reasoning on Unification in Inductive Logic Programming -- Coalition Structure Generation with GRASP -- Machine Learning, Data Mining, and Information Retrieval -- A Bayesian Model for Entity Type Disambiguation -- The Impact of Valence Shifters on Mining Implicit Economic Opinions -- Entity Popularity on the Web: Correlating ANSA News and AOL Search -- Using Machine Learning to Prescribe Warfarin -- Single-Stacking Conformity Approach to Reliable Classification -- A Relative Word-Frequency Based Method for Relevance Feedback -- AI in Education -- Sequence Detection for Adaptive Feedback Generation in an Exploratory Environment for Mathematical Generalisation -- A Deep Insight in Chat Analysis: Collaboration, Evolution and Evaluation, Summarization and Search -- Ontology-Based Authoring of Intelligent Model-Tracing Math Tutors -- Applications -- Comparative Analysis of Distributed, Default, IC, and Fuzzy ARTMAP Neural Networks for Classification of Malignant and Benign Lesions -- An Adaptive Approach for Integration Analysis of Multiple Gene Expression Datasets -- EVTIMA: A System for IE from Hospital Patient Records in Bulgarian -- Direct Field Oriented Neural Control of a Three Phase Induction Motor -- General Shape Analysis Applied to Stamps Retrieval from Scanned Documents -- Posters -- Selection of Foundational Ontology for Collaborative Knowledge Modeling in Healthcare Domain -- Towards Ontological Blending -- Integration of Ontology with Development of Personalized E-Learning Facilities for Dyslexics -- A Meta Learning Approach: Classification by Cluster Analysis -- Mapping Data Driven and Upper Level Ontology -- Data Sample Reduction for Classification of Interval Information Using Neural Network Sensitivity Analysis -- Individualized Virtual Humans for Social Skills Training -- Signal Classification with Self-organizing Mixture Networks -- Simulation of the Autonomous Agent Behavior by Autoregressive Models -- Semi-partitioned Horn Clauses: A Tractable Logic of Types -- Feed Rate Profiles Synthesis Using Genetic Algorithms -- An Ontology of All of Computing: An Update on Challenges and Approaches.
Keywords: Computer science; Computer Communication Networks; Database management; Data mining; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Database Management; Computer Communication Networks; Data Mining and Knowledge Discovery